Contributions to Polar Eskimo Ethnography. - Holtved, Erik (Meddelelser om Grønland, 1967)
The paper presents the ethnographic observations made in connection with archeological, linguistic, and folkloristic work undertaken during stays with the Polar Eskimos during the years 1935- 37 and 1946- 47. The descriptions are devoted in most detail to conditions of dwelling, hunting, fishing, and craft, but by and large should convey a general impression of the conditions in the Thule district at the beginning of this century, when especially the missionaries and the establishment by KNUD RASMUSSEN of the Thule Station have placed their stamp on the existence.